"Reverberating Echoes: Contemporary Art Inspired by Traditional Islamic Art": Graduate Theological Union, Berkeley, California, 31 January 31–26 May 2017. Issue 2 (3rd April 2017) - Séquin, Carlo H.
Abstract :